Inclusive Leadership, Meaningful Work, and Midwives’ Contraceptive Access Service Performance: The Mediating Role of Psychological Capital - Lilis Setyowati; Untung Lasiyono; Yusuf Iskandar (Women, Education, and Social Welfare, 2026)
This study examines whether inclusive leadership and meaningful work enhance midwives’ performance in delivering contraceptive access services and whether psychological capital explains these relationships. A cross-sectional explanatory survey was conducted among 100 practicing midwives affiliated with 39 Independent Midwifery Practices (TPMBs) in Cengkareng, West Jakarta. Data were analyzed using partial least squares structural equation modeling. All constructs demonstrated adequate convergent validity (AVE = 0.584–0.653) and strong internal consistency (composite reliability = 0.944–0.958; Cronbach’s α = 0.935–0.952). Inclusive leadership positively predicted performance (β = 0.336) and psychological capital (β = 0.474), while meaningful work predicted performance (β = 0.194) and psychological capital (β = 0.509). Psychological capital was positively associated with performance (β = 0.459). The indirect effects of inclusive leadership (β = 0.218) and meaningful work (β = 0.234) were significant. Because both direct and indirect paths remained positive and significant, psychological capital operated as complementary partial—not full—mediation. The model explained 85.5% of psychological capital and 88.5% of performance variance. The findings position inclusive, psychologically enabling management as a human-centered pathway to more responsive contraceptive access services for women.